Unlocking the limitedness on promotion: Augmenting a web-based mobile promotional media for delivery services at a homeware company - Normaliza, Normaliza; Adi, Novi Hendri; Putri, Weni Lestari; Zar, Win Thu (Journal of Computer-based Instructional Media, 2024)
As information technology develops, the utilization of the internet as a business platform has increased significantly, allowing companies to promote their products and services more widely and efficiently. This research explores the development of a mobile website for a homeware company in Batam, which currently relies on online platforms such as Shopee and Tokopedia. This dependency causes limitations in reaching customers optimally. Therefore, this research proposes the development of mobile web-based promotional media using the Waterfall method, which includes the stages of need analysis, system design, implementation, testing, and maintenance. This method was chosen to ensure a systematic approach in designing and developing a responsive and appropriate website. Using Unified Modeling Language (UML) in system design possibly allows clear visualization and effective stakeholder communication. The implementation conducted by employing PHP, MySQL, and CodeIgniter framework resulted in a website which is expected to be able to fulfil the functional and non-functional needs of the company. The results show that developing this mobile web-based promotion system can potentially increase the company's market reach and operational efficiency as well as provide easy access for customers. This research provides an innovative model for similar companies to adopt digital technology to improve their business competitiveness.